Hadith #678 - Sahih al-Bukhari - 'Ubaid-Ullah bin Adi bin Khiyar (Sahih al-Bukhari)
I went to ‘Uthman bin Affan while he was besieged, and said to him, “You are the chief of all Muslims in general and you see what has befallen you. We are led in the Salat (prayer) by a leader of Al-Fitan (trials and afflictions etc.) and we are afraid of being sinful in following him.” ‘Uthman said. “As-Salat (the prayers) is the best of all deeds so when the people do good deeds do the same with them and when they do bad deeds, avoid those bad deeds.” Az-Zuhri said, “In our opini
Grade: Sahih